Local Ecological Knowledge on Food Materials of Land Plant Origin in Kabola Ethnic Communities in Alor District, East Nusa Tengara Province - Sanherip Laalobang; I. W. Mudita; Yosep Seran Mau (Jurnal Ilmu Lingkungan, 2021)
Local Ecological Knowledge (LEK) regarding local food plants is knowledge that is owned by local communities and is passed down from generation to generation. LED is obtained through a long process of adaptation and is used by local communities to address environmental problems. The Kabola ethnic group also has LEK regarding food plants used to solve food problems on dry land, but the LEK owned by the Kabola ethnic community is in danger of being lost. The method used is a mixed method (Mixed Methodology), which combines qualitative methods and quantitative methods, data collection begins with an exploration using a qualitative case study method by means of in-depth interviews followed by a quantitative survey method of the plant species mentioned during the interview. The results showed that the Kabola ethnic group still collects wild food plants from forests, former gardens and riverbanks, even though they have cultivated various types of food crops; The Kabola ethnic group community collects food plants during the rainy season and dry season, but most food gathering activities are carried out at the end of the rainy season and during the dry season; The people of the Kabola ethnic group collect food by using simple tools while leaving certain parts of the plant from which the food is collected; The people of the Kabola ethnic group still pass on local knowledge about foodstuffs to the younger generation through stories, personal experiences and providing examples or direct practices about plants that can be used to meet food needs; The Kabola ethnic group cultivates local food plants, but these cultivation efforts are only carried out individually and have not received support from the local government.